PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PARIGI KOTA - TOLIS, MEGA DELFIANA (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to determine whether Job Satisfaction and Organizational Commitment simultaneously or partially affect the Performance of employees at the Office District Parigi City. This study uses quantitative research which aims to explain the relationship between two or more variables with the sample of all employees at the Parigi City District Office amounting to 39 people and data analysis techniques used is multiple linear regression analysis. The results of hypothesis analysis and testing can be concluded bawha: (1) berdasarka regression test results obtained Sig. F of 0.000 <?0.05 which can be interpreted that the variable Job Satisfaction and Organizational Commitment simultaneously significant to the performance of employees. (2) based on the regression test results obtained variable Job satisfaction has a significance level t sig. 0,003 <? 0,05 can be interpreted that job satisfaction variable partially have an effect on signifikan to employee performance. (3) based on regression test results obtained variable Organizational commitment has significance level t sig. 0,033<? 0,05 can be interpreted that variable of Commitment of organization partially have an effect on signifikan to employee performance.